Perencanaan Ulang Struktur Bawah Gedung dengan Fondasi Tiang Pancang: Studi Kasus Proyek Pembangunan Rumah Susun Pekerja Industri Batang III JTGRSN21-03 - Abimanyu Wahyu P.S.P.; Adi Prasetyo Pambudi; Soedarsono Soedarsono; Lisa Fitriyana (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Pile foundations play an important role in ensuring the stability of multi storey buildings subjected to axial loads, lateral loads, and moments. In the Batang III Industrial Worker Housing Project (JTGRSN21-03), the original foundation system used bored piles. This study redesigns the foundation into spun piles with a diameter of 0.80 m and a length of 12 m under the same soil conditions and loads. The research methodology was conducted through analysis of three foundation joints. Axial bearing capacity was evaluated using the Meyerhof method, resulting in a tip resistance of 946.00 kN, skin friction resistance of 2,970.37 kN, ultimate bearing capacity of 3,916.37 kN, and allowable bearing capacity of 1,305.46 kN. Lateral bearing capacity was analyzed using the Broms method with an allowable capacity of 162.0 kN. Group pile bearing capacity was determined using the Converse Labarre method. Settlement analysis using the Vesic method showed a single pile settlement of 22.69 mm and group settlements of 50.2 mm at joint 599, 41.8 mm at joint 628, and 21.0 mm at joint 371. Plaxis analysis produced smaller settlements of 13.94 mm, 13.44 mm, and 9.19 mm. The pile cap and shear wall design is considered safe.